Effect of starch on surface properties of pyrite and chalcopyrite and its response to flotation separation at low alkalinity. (November 2019) - Han, Guang; Wen, Shuming; Wang, Han; Feng, Qicheng
Graphical abstract: Highlights: Flotation separation of chalcopyrite from pyrite was achieved at low alkalinity. Starch strongly affected the surface properties of pyrite, but had only a slight effect for chalcopyrite. Starch adsorbed onto the pyrite surface via both physical and chemical adsorption. Starch interacted strongly with Fe sites on the pyrite surface, but only slightly with those on chalcopyrite. Abstract: The interaction behavior and mechanism of starch with pyrite and chalcopyrite surfaces and its effect on their flotation separation at low alkalinity were investigated by micro-flotation tests, zeta potential measurements, infrared spectroscopy, and X-ray photoelectron spectroscopy. The micro-flotation tests showed that starch exhibited an obvious depressive effect on pyrite, but not on chalcopyrite. Zeta potential measurements indicated that starch reduced the surface potential of pyrite, but had no significant effect on the surface electrical properties of chalcopyrite within a wide pH range. The infrared spectra showed that new characteristic peaks appeared after the pyrite surface was treated with starch, suggesting that starch could significantly interact with pyrite particles. The adsorption mechanism of starch onto the mineral surface was further ascertained by X-ray photoelectron spectroscopy, which revealed that starch interacted strongly with Fe sites on the pyrite surface, but only slightly with those on chalcopyrite. These results showed that starch strongly affected the surface properties of pyrite, but had only a slight effect for chalcopyrite. Use of starch as a depressant therefore enabled the flotation separation of chalcopyrite from pyrite at low alkalinity.